2010
DOI: 10.1093/gerona/glq001
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Water May Mask Actual Muscle Atrophy During Aging

Abstract: The ECW/TW ratio increases in the lower leg with age. The results suggest that the expansion of ECW relative to ICW and the LV masked actual muscle cell atrophy with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
154
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(158 citation statements)
references
References 31 publications
4
154
0
Order By: Relevance
“…The use of a single-frequency BIA equipment could be a limitation in our study. Skeletal muscle holds water which is partitioned in intracellular and extracellular water, and changes in the ratio occur with aging (Yamada et al, 2010). Besides, single-frequency BIA is strongly influenced by relative expansion of ECW and overestimates skeletal muscle cross sectional area in the elderly (Yamada et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a single-frequency BIA equipment could be a limitation in our study. Skeletal muscle holds water which is partitioned in intracellular and extracellular water, and changes in the ratio occur with aging (Yamada et al, 2010). Besides, single-frequency BIA is strongly influenced by relative expansion of ECW and overestimates skeletal muscle cross sectional area in the elderly (Yamada et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a reduced attenuation coefficient on CT of midthigh and lower leg muscle was a predictor of poor muscle strength and functional limitations independently of muscle CSA (Goodpaster et al 2001;Sipilä et al 2004;Visser et al 2002). These reports suggest that the evaluation of age-related changes in muscle quantity results in an overestimation of the amount of contractile muscle in older persons (Goodpaster et al 2001;Sipilä et al 2004;Visser et al 2002;Yamada et al 2010). In studies using ultrasound images, Suominen (1991, 1994) reported that EI of the quadriceps femoris was significantly correlated with knee extensor strength in older persons.…”
Section: Introductionmentioning
confidence: 95%
“…By the fourth decade populations (1,9) and individuals (10) begin to show a gradual loss in skeletal muscle mass and the rate of atrophy appears to accelerate beyond the seventh decade (1,9,11) . These later years are associated with sarcopenia and related functional loss of skeletal muscle, often referred to as dynapenia (12) , that together reflect skeletal muscle's loss in mass, altered composition (13,14) and lowered functionality as defined by strength and *Corresponding author: S. B. Heymsfield, email Steven.Heymsfield@pbrc.edu Abbreviations: ALST, appendicular lean soft tissue; BIA, bioimpedance analysis; CT, computed tomography; DCR, deuterated creatine; DXA, dualenergy X-ray absorptiometry; HU, Hounsfield units; IMAT, intermuscular adipose tissue; SEE, standard error of the estimate.…”
mentioning
confidence: 99%